Case report: desensitization of hypersensitivity against the antisense oligonucleotide volanesorsen - Isaac, Rafael H.; Gonzalez-Devia, Deyanira; Mendivil, Carlos O.; Chapman, Edgardo (Frontiers in Allergy, 2023)
Abstract Familial chylomicronemia syndrome (FCS) is a rare autosomal recessive metabolic disorder that causes extremely elevated plasma triglyceride levels, with limited therapeutic options. Volanesorsen is an antisense oligonucleotide approved for its treatment. A 24-year-old woman with genetically diagnosed FCS secondary to a pathogenic variant in APOA5 and a history of recurrent hypertriglyceridemia-induced pancreatitis episodes was being treated with volanesorsen, 285 mg every two weeks. Treatment with volanesorsen achieved normalization of triglycerides to <200 mg/dL. However, after the fifth dose of the medication the patient developed urticaria and volanesorsen was discontinued. In the absence of alternative pharmacological treatments, the patient received a novel desensitization protocol for volanesorsen that allowed continuation of therapy, without evidence of hypersensitivity reactions after subsequent administrations. FCS requires aggressive multimodal therapy and close follow-up. Volanesorsen has shown great efficacy, but a significant rate of discontinuation due to side effects has been observed. Here, the patient presented an immediate hypersensitivity reaction to volanesorsen, but the provision of a desensitization protocol was effective, facilitating continued treatment and impacting the survival and quality of life of the patient.